You - Drvenkar, Zoran, 1967- author; Whiteside, Shaun, translator (London : HarperCollinsPublishers, 2014)
The chilling new thriller by the author of SORRY When a snowstorm halts traffic on a German autobahn, drivers are forced to spend the night in their cars. As day breaks, scores of people are found dead. Theories are rife. Was it an argument? Was it drugs, revenge or madness? At first everyone agrees that several people must have acted together. No-one could have committed such an atrocity alone. It is only over time that theories come to focus on an individual perpetrator, and the Traveller is born. As he makes his way across a country gripped by fear, he's searching for his next victim ...You